SPECIFIC ASPECTS OF THE ACTIVITY OF REPRESENTATIVES OF THE QADIRIYA SECT EXISTING TODAY - Bekzodbek Muxtarov (American Journals, 2023)
This article analyzes the modern form and characteristics of Qadiriya sect, one of the global sects whose activities are being observed today.
Keywords: Sufism, tariqa (order), Qadiriya, leech, pir, teacher, leader, region, silsila, shahabcha.